2020
DOI: 10.7554/elife.54318
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin rejuvenates oral health in aging mice

Abstract: Periodontal disease is an age-associated disorder clinically defined by periodontal bone loss, inflammation of the specialized tissues that surround and support the tooth, and microbiome dysbiosis. Currently, there is no therapy for reversing periodontal disease, and treatment is generally restricted to preventive measures or tooth extraction. The FDA-approved drug rapamycin slows aging and extends lifespan in multiple organisms, including mice. Here, we demonstrate that short-term treatment with rapamycin rej… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 51 publications
1
45
0
Order By: Relevance
“…The short course of treatment resulted in significantly increased alveolar bone compared with age-matched controls, which was also associated with a local decrease of nuclear factor kappa light chain enhancer pro-inflammatory signaling within the periodontium. 160 Interestingly, the same study showed that the short course of rapamycin treatment resulted in new bone formation, as the treated groups had significantly more alveolar bone compared with pretreatment levels for the same animal (as measured by in vivo micro-computed tomography). 160 In summary, these results suggest that targeting mammalian target of rapamycin may be a future treatment strategy for periodontal disease in older patient populations.…”
Section: Mammalian Target Of Rapamycin and Agingmentioning
confidence: 91%
See 3 more Smart Citations
“…The short course of treatment resulted in significantly increased alveolar bone compared with age-matched controls, which was also associated with a local decrease of nuclear factor kappa light chain enhancer pro-inflammatory signaling within the periodontium. 160 Interestingly, the same study showed that the short course of rapamycin treatment resulted in new bone formation, as the treated groups had significantly more alveolar bone compared with pretreatment levels for the same animal (as measured by in vivo micro-computed tomography). 160 In summary, these results suggest that targeting mammalian target of rapamycin may be a future treatment strategy for periodontal disease in older patient populations.…”
Section: Mammalian Target Of Rapamycin and Agingmentioning
confidence: 91%
“…160 Interestingly, the same study showed that the short course of rapamycin treatment resulted in new bone formation, as the treated groups had significantly more alveolar bone compared with pretreatment levels for the same animal (as measured by in vivo micro-computed tomography). 160 In summary, these results suggest that targeting mammalian target of rapamycin may be a future treatment strategy for periodontal disease in older patient populations. In addition, the findings further implicate periodontal disease as an age-related disease by showing that targeting a dysregulated pathway central to the aging process (mammalian target of rapamycin) improves periodontal health.…”
Section: Mammalian Target Of Rapamycin and Agingmentioning
confidence: 91%
See 2 more Smart Citations
“…In rodents, for example, it has been shown that the drug rapamycin can prevent age-related diseases and improve function in multiple aged tissues and organs. Now, in the eLife special issue on aging, An et al report that rapamycin also works in the oral cavity and can reverse periodontal disease in mice ( An et al, 2020 ). Other articles suggest translational strategies to target specific hallmarks of aging for intervertebral disc degeneration ( Cherif et al, 2020 ) and age-related heart disease ( Chiao et al, 2020 ).…”
mentioning
confidence: 99%